PERANCANGAN DAN PEMBUATAN APLIKASI PENGANGGARAN BEA CUKAI TANJUNG PANDAN DENGAN METODE UML - Mohamad Firdaus; Indra Bakti (CV. Adiba Aisha Amira, 2024)
Tanjung Pandan Customs Office as a state institution has the opportunity to compete with other customs offices in Indonesia, as an added value for the assessment of the Tanjung Pandan Customs office in its assessment in the Customs Institution. SIMPORA as an information system for Budget Absorption and Realization or budgeting is made to meet these needs. In the design of this budgeting application built with the Unified Software Development Process framework as well as in making this software application using the Unified Modeling Language (UML) method. In its creation, the search for Software Requirements Specifications (SKPL) is based on the interview method, then proceeds with the creation of a Software Design Design (DPPL), then followed by application creation and closed with testing. And in this study also displayed the final results of the software. The result of this project is software that is also equipped with design and application documentation whose ultimate goal is to give the Tanjung Pandan Customs office a winner in the competition between customs offices throughout Indonesia.